WELL INTEGRITY ANALYSIS ON COLD WATER FRACTURING IN SLIM HOLE GEOTHERMAL WELL - Rizkika Ruanawijaya, Nanda
Indonesia is at the junction of three tectonic plates which play a role in forming Indonesia's volcanic mountains. This source of magma from the mountains becomes a source of heat, making Indonesia one of the countries with the largest geothermal reserves in the world. In the midst of the transition from using fossil energy to renewable energy, the development of geothermal fields has increased quite significantly. However, geothermal field locations are usually in remote areas so that conventional equipment commonly used for oil and gas fields cannot be used for exploration and production activities. Slim hole wells are the choice of Sembalun field developers, especially at Well Y. Production has continued to decline in the last two years. The field developers decided to use hydraulic fracturing with cold water injection to increase production. However, it needs to be further analyzed whether the tubular at well Y is able to withstand the load received due to the use of hydraulic fracturing. Therefore, this study focuses on analyzing the ability of slim hole wells to withstand loads due to high temperatures from geothermal reservoirs and loads due to the implementation of hydraulic fracturing. This study will ultimately produce recommendations for the use of slim hole wells and solutions for the failure of wells to withstand loads. Based on the calculation results, the reservoir temperature affects the yield strength of the intermediate casing, production casing and liner to 53052.08, 49309.03, and 46177.89 psi. The calculation of the pressure on the tubular without considering the effect of axial pressure is carried out and shows that the tubing is able to withstand the pressure. Meanwhile, with the effect of axial pressure on the burst and collapse rating, the intermediate and production casing are able to withstand the collapse load, but not the burst load. Meanwhile, the liner is not able to withstand burst loads and also collapse. After that, a triaxial pressure analysis is also performed by calculating von mises equivalent. The results show that yielding occurs in all slim hole used. The incapability of Schedule 40 casing to withstand load, bringing up a recommendation to change the grade of casing to M - 65 for intermediate casing and X - 80 for production casing and liner. In addition, modification of production parameters can also be carried out to reduce the rate of geothermal production, so that slim hole wells are able to withstand the pressure received. Sensitivity on Pump Pressure, Fracture Gradient and Wall Thickness Tolerance was conducted to determine which value is allowed to be modified.